2023
DOI: 10.5267/j.uscm.2023.2.014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ACs and their impact on the period of issuing the auditor’s report: An Empirical study on Jordanian public shareholding companies

Abstract: This study aimed to examine the characteristics of audit committees (ACs) on the short delay in issuing audit reports. Using data for 97 companies in the industrial and service sectors in the Jordanian context, for the period between 2017 and 2021. The results of this study showed that the independence of ACs has an important and negative impact on reducing the delay in issuing financial reporting (FR). However, the study did not find the importance of the rest of the characteristics related to ACs to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022; Yasser et al ., 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023; Shah et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022; Yasser et al ., 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023; Shah et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shamsuddin and Alshahri (2022) found that in Oman, the number of annual meetings held is more than the Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022;Yasser et al, 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023;Shah et al, 2022). Our results demonstrate a higher effect of AC independence in developing countries which is in line with previous research that has shown that audit committee (AC) independence is more important for developing countries than developed countries (Biswas et al, 2023).…”
Section: Audit Committee and Firm Performancementioning
confidence: 99%